Adhesion and Inhibition of Streptococcus mutans by Electrospun Fibers Containing Propolis for Fast Dissolving Dosage Form - Chawalinee Asawahame (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this study was to prepare orally fast dissolving fibers using anelectrospinning process with hydrophilic polymers.Propolis extract was used as an active ingredient, volatile oils such as eucalyptus oil, methyl salicylate, menthol and thymol were used as flavoring agents, while Tween 80 was used as wetting agent in the formulation. The antimicrobial activity of propoliselectrospun fibers against Streptococcus mutans which is the major bacteria for inducing tooth decay and plaque formation was studied. The inhibition of adherence of S.mutansto smooth glass surface by propoliselectrospun fibers was also studied and compared with commercial mouthwash solutions. Three kinds of hydrophilic polymers were studied using polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA)andhydroxypropyl cellulose (HPC) to arrive at a suitable polymer and its optimum condition for fiber formation. This investigation used different types and molecular weights of polymers (PVP K90, PVP K30, PVA MW 85,000-146,000, PVA MW 47,000 and HPC MW 370,000) to influence the spinnability of the polymer solution, and thus the morphology of the electrospun fibers. The morphology of electrospun fibers was influenced by various solution parameters (viscosity, conductivity, surface tension) and process parameters (electric field strength, flow rate, collector type). It was found that PVP K90 at 8–10% (w/v) in ethanol with the following spinning conditions,generated electrospun fiberswith appropriate quality and stability:a distance between the needle tip and the collector of 15 cm, a voltage supply of 15kV, anda feed rate at 2 mL/hr. Propolis-PVP electrospun fibers were successfully prepared using the above electrospinning technique. Incorporated propolisup to 5% (w/v) in PVP K90 polymer solution was able to produce smooth, uniform and free-bead electrospun fibers with diameters ranging around 1.2 – 1.4 m. 1% (w/v) Tween80 was used as wetting agent for improved wettability of electrospun fibers which were incorporated into the propolis. Propolis-PVP electrospun fibers can be disintegrated and dissolved in small amounts of water.The antibacterial activities from Propolis-PVP electrospun fibers against S. mutans when tested through agar diffusion revealed an inhibition zone when tested with a concentration of propolis from electrospun fibers equivalent to 10 MIC and above (propolis extract used in this study showed MIC at 1.172 mg/mL). Electrospun fibers of 5% (w/v) propolis with 8% (w/v) PVP electrospun fibers with or without additives and Tween80,were tested at a concentration of propolisequivalent to 0.6 MIC and 1 MIC an this reduced the adherence of S. mutanstoa smooth glass surface with more than 50%. The resultproved that propolis extract in electrospun fibers at 0.6 and 1 MIC aremore effective thancommercial mouthwash solutions containing natural essential oils as active ingredientsthat were free from chemical antiseptic substances but were, however, less effective than the mouthwash solutions containingsome chemical substances as antiseptic agents. In conclusion, the present study has demonstrated that propolis-PVP electrospun fibers can be used as fast dissolving fibers to control S. mutans in oral cavities. Propolis-PVP electrospun fiber matscan be used as an alternative anticariogenic agent,and in a newsolid dosage form.